Evaluation of Supplier Performance Using The Fuzzy AHP Approach to The CV. X Bandung Kite Glass Business - Anggraito, Hendry (Universitas Insan Cendekia Mandiri, 2024)
One of the efforts to deal with the high level of business competition in the kite glass industry in Indonesia is to improve the quality of raw materials and optimize all available resources. However, internal improvements in the company are not enough, so the participation of all parties is needed, starting from suppliers who supply raw materials from China to Indonesia, namely to companies and feedback from kite glass craftsmen as users of these raw materials into finished products so that the quality of goods is in accordance with what is expected. desired by kite glass craftsmen in general as well as the distribution network that will deliver the product to the hands of the customer. In this regard, it is necessary to periodically evaluate suppliers so that the raw materials and products received by the company are in accordance with price, quality and delivery. This study aims to evaluate three suppliers and choose the best according to predetermined criteria and sub-criteria. To get the priority weight value for supplier assessment, researchers used the AHP fuzzy method.